2014
DOI: 10.1016/j.crohns.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the diagnosis and management of IBD-associated anaemia and iron deficiency in Germany: The German AnaemIBD Study

Abstract: Although intravenous iron supplementation is recommended in IBD patients, current German practice still relies on oral therapy, even in severe anaemia. The high incidence of severe anaemia in this cohort reflects inadequate iron replacement and status monitoring. While the proportion of IBD patients with inadequately treated anaemia/iron deficiency is unknown, greater awareness of existing guidelines for iron deficiency management in IBD patients appears necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
1
28
1
4
Order By: Relevance
“…These findings are in agreement with other recent reports on the management of IBD patients diagnosed with anemia. A recent study from 55 German gastroenterological centers showed that only 43.5% of anemic IBD patients were treated for anemia (28). In another study from 9 European countries the majority of IBD patients with anemia were treated with oral iron (67%) whereas only 28% received IV iron (29).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with other recent reports on the management of IBD patients diagnosed with anemia. A recent study from 55 German gastroenterological centers showed that only 43.5% of anemic IBD patients were treated for anemia (28). In another study from 9 European countries the majority of IBD patients with anemia were treated with oral iron (67%) whereas only 28% received IV iron (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Blumenstein et al revealed that in Germany 56.5% of IBD patients with anemia had not received adequate treatment [19]. Likewise, a web-based questionnaire of IBD patients showed that one third of those with anemia had not been treated accordingly [15].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, clinicians usually underestimate anemia in IBD patients 13 . A German survey among gastroenterologists found that more than 50% of patients with IBD-associated anemia were not treated, or were undertreated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%